Legal Politics of Regional Boundary Line Regulation - Firdausi, Firman; Shandra Dewi, Dewa Ayu Putu; Trihardiyanto, Willy (Jurnal Cakrawala Hukum, 2024)
Spatial planning in Indonesia is a challenge in its implementation. Plans that have been set do not always run as they should. Regulating public space is not as easy as regulating private space, mainly when existing conditions exist first or what has happened cannot be returned just like that. Existing conditions are non-retroactive or do not apply retroactively, so existing conditions do not match what was planned. Regulating asymmetric conditions like this requires a wise regulatory mechanism. This study used normative juridical. This is because the existing boundary line rules in the region are still unclear. The area studied here is Jombang Regency, where, during this study, regional regulations on boundary lines still do not exist or have been ratified. The study results showed that the Jombang Regency Government is designing regional regulations on boundary lines. The application of boundary lines considers existing provisions so that certain areas or roads need to be adjusted based on current conditions so that they do not harm the community due to the issuance of regulations on boundary lines.